The Effectiveness of Nurse‐Led Transition Care on Post‐Discharge Outcomes of Adult Stroke Survivors: A Systematic Review and Meta‐Analysis - Nyagwaswa Athanas Michael; Lilian Teddy Mselle; Edith Mroso Tarimo; Yingjuan Cao (Nursing Open)
ABSTRACT Aim To evaluate the effectiveness of nurse‐led Transition Care (TC) on quality of life, mortality and readmission among adult stroke survivors. Design Systematic review and meta‐analysis using the Joanna Briggs Institute (JBI) methodology for systematic reviews of effectiveness. Methods Databases were searched from 1st January 2000 to 31st December 2023. Search was done in Medline, Science Direct, Scopus, EBSCOhost, Web of Science and Cochrane Library and Central Registry of Clinical Trials. The randomised controlled trials that assessed the effectiveness of nurse‐led TC for adult stroke survivors were included. The primary outcome was 1‐year quality of life, whereas the secondary outcomes were mortality and readmission. Two independent reviewers performed data extraction and quality appraisal by using the JBI methodology. Random effect models and pre‐specified subgroup analyses were performed using Review Manager Software Version 5.3. and STATA Version 17. Results Of 1093 studies retrieved from database search, only 18 studies met the review inclusion criteria. The pooled results show that stroke survivors who were allocated to nurse‐led TC programs had a 1‐year better quality of life compared to those allocated to usual care (12 studies; SMD = 0.52; 95% CI = 0.20, 0.85; p = 0.002; I2 = 94%). However, no significant differences in the odds of mortality and readmission were observed. No patient or public contribution.